Atualização em Cirurgia Neoplásica do Tórace - Burnier, E. M. Penido (2023)
The author delineate the clinicai orientation followed in thoracic surgery at the National Institute of Câncer; shows surgical technics and orientation in pre and post operative procedures are variations from Swett and Pach tecnics. Defend the left toracotomie for the esophagus surgery. Insists in the lose time attempting the etiologic diagnosis when by explorated thoracotomie is the best method by intra-operatorie biopsis. Radiotherapy and Chemotherapy are used only for inoperable cases incomplet surgery or recurrent cases.